Development of cross-section calculation module for high-temperature gas-cooled reactor engineering simulator system using an optimal model tree algorithm. (May 2023) - Tan, Kai; Liu, Meidan; Wei, Chunlin
Highlights: A more accurate cross-section calculation model is required for real-time simulation. A machine-learning-based cross-section calculation model is proposed. The proposed method produced accurate cross-section and reactor physics results. It also met the engineering simulator system real-time calculation requirements. Under different operating conditions it conformed to the reactor laws of physics. Abstract: To improve the accuracy of reactor physics module in the high-temperature gas-cooled reactor engineering simulator system (HTGR-ESS), a more accurate cross-section calculation model is required under the premise of real-time calculation in the simulation. Due to the nonlinear relationship between cross-section and reactor state parameters, such as burnup, moderator temperature and fuel temperature, etc., it is difficult to achieve full-range accuracy using the current multiple linear regression method (MLR). In this study, a machine-learning-based cross-section calculation model for the reactor physics model is proposed. We made improvements to the model tree by setting a smoothing function on the boundary and using ridge regression at the leaf node to conduct a continuous cross-section calculation model without overfitting in the subspace over the full range, trained from a scattered database generated by V.S.O.P. In the numerical tests, the proposed method produced far more accurate cross-section and reactor physics calculation results than the current method and could also meet the real-time calculation requirement. Meanwhile, the responses of the power and helium outlet temperatures of the 10 MW HTGR (HTR-10) simulator under different operating conditions conform to the reactor laws of physics, further validating the applicability of the proposed method.